Protein quality control systems in neurodegeneration – culprits, mitigators, and solutions? - Ciechanover, Aaron; Livneh, Ido (Frontiers in Neurology, 2025)
A key hallmark of neurodegenerative diseases (NDDs) is the formation of neurotoxic protein aggregates, which are considered to reflect inadequate protein quality control (PQC). In agreement with this fundamental pathophysiologic characteristic, the two main cellular systems responsible for cellular protein removal – the ubiquitin-proteasome system (UPS) and autophagy – have been extensively studied in the context of NDD. The involvement of these proteolytic machineries was interpreted in different ways – some pointed them as dysfunctional systems that may underlie pathogenesis, while others suggested they fulfill protective roles which delay the clinical presentation of these diseases. Perhaps not surprisingly, the growing body of knowledge concerning the different types of NDD portrays a more complex picture, and no distinct generalization can be made regarding the contribution of either the neurotoxic protein substrate(s) or proteolytic system(s) to the development of NDD. For instance, in Parkinson’s disease, the toxic aggregation of α-synuclein, Parkinson’s canonical culprit protein, can stem from seemingly unrelated events. Among them, alterations in α-synuclein itself, a mutation in Parkin – an E3 ubiquitin ligase targeting proteins and organelles to proteasomal and lysosomal degradation, respectively, as well as a mutation in LRRK2 – a kinase postulated to be linked with α-synuclein through their common removal by chaperone-mediated autophagy. Also, in amyotrophic lateral sclerosis (ALS) and frontotemporal lobar degeneration (FTLD), the toxic aggregation of one protein – TDP-43 – can result from defects in other proteins, some of which are related to proteostasis, such as the shuttle protein Optineurin and the E3 ubiquitin ligase VCP. In contrast, ALS and FTLD demonstrate how common abnormalities leading to neurotoxic aggregate formation, may present clinically in profoundly different ways, from motor dysfunction to behavioral changes. In Alzheimer’s Disease, the leading cause for dementia, rare cases were linked directly with PQC as they are caused by a mutation in one of the genes encoding ubiquitin itself, while the majority of cases were not directly linked to components of the two main proteolytic systems. All-in-all, the UPS and autophagy are heavily intertwined with NDD, either as part of the problem or as mitigating factors, and hopefully – as platforms for future therapeutics. In this review, we shall dissect NDDs from the perspective of protein turnover pathways, aiming to track both common and unique patterns of PQC failure in this group of diseases, which differ significantly from one another both in their clinical manifestations and affected anatomic regions, yet share the common trait of abnormal protein accumulation. We shall review some of the mechanistic understandings concerning protein aggregation in NDDs, describing the interactions of aggregated proteins with the UPS and autophagy, discuss recent controversies around the protein aggregates’ hypothesis, and point to implications for developing therapeutic strategies.